Effects of Acupuncture-moxibustion on Monocyte Th1/Th2 Cytokine in Peripheral Blood of Patients with Perennial Allergic Rhinitis - 郑美凤 林诚 郑良朴 何芙蓉 (Journal of acupuncture and tuina science, 2010)
Objective To observe the effects of acupuncture-moxibustion on symptoms, signs, and Th1/Th2 cytokine, and regulation on Th1/Th2 in patients with perennial allergic rhinitis(PAR) to provide experimental basis for acupuncture treating allergic rhinitis and investigate the mechanism. Methods Thirty patients with allergic rhinitis were treated with acupuncture-moxibustion, and 30 healthy cases were the control. Clinical symptoms, signs, and nasal mucosa were observed, and contents of IL-4, IFN-γ, and granulocyte-macrophage colony stimulating factor (GM-CSF) in the supernatant of peripheral blood monocyte cultured with PHA by ELISA, before treatment, after one course of treatment, and after two courses of treatment. Results Before the treatment, the contents of IL-4, and GM-CSF were higher ( P <0.01) and IFN-γ was lower ( P <0.01) in the PAR cases than in the control cases. In the PAR cases, the content of GM-CSF was positive correlation with that of IL-4 ( P <0.01), and negative correlation with IFN-γ ( P <0.01). After the treatment, contents of IL-4 and GM-CSF were lowed ( P <0.01), content of IFN-γ was increased ( P <0.05), and all IL-4, GM-CSF and IFN-γ had no difference compared with those in the control cases. Conclusion Acupuncture-moxibustion could improve the symptoms and signs in PAR patients, enhance the immune function. It may be achieved by regulating the expression of Th1 and Th2, correcting the imbalance of Th1/Th2.